Population migration pattern in China: present and future - Lu,Qi; Söderlund, Leif; Wang,Guoxia; Duan,Juan (MTT, 2005)
This paper explores the population pattern in China since the 1990s, as it plays a significant role in the process of urbanization and modernization. At present, China is experiencing nationwide population redistribution. There have been big increases in both intra-province and inter-province migration relative to the situation in the 1980s, especially in the case of cross-region migration. The data show that Eastern China is the main destination for migration, particularly the Pearl River Delta, Yangtze River Delta and Bosea Economic Circle. It is the increase in surplus rural labour, the heightened disparity between rural and urban incomes and between inland and coastal incomes, and institutional changes that have contributed to the current population pattern of migration. In the last twenty years there has been only a small change in the migration pattern, with the Markov Chain, that is the Pearl River Delta taking a smaller share of the migrants and more of them being concentrated in the Yangtze River Delta.
Keywords: Ys; Kiina; muuttoliike; migration; migration patter; China